Mitotic Inheritance of mRNA Facilitates Translational Activation of the Osteogenic‐Lineage Commitment Factor Runx2 in Progeny of Osteoblastic Cells. Issue 5 (18th September 2015) - Varela, Nelson; Aranguiz, Alejandra; Lizama, Carlos; Sepulveda, Hugo; Antonelli, Marcelo; Thaler, Roman; Moreno, Ricardo D.; Montecino, Martin; Stein, Gary S.; van Wijnen, Andre J.; Galindo, Mario
Abstract : Epigenetic mechanisms mediate the acquisition of specialized cellular phenotypes during tissue development, maintenance and repair. When phenotype‐committed cells transit through mitosis, chromosomal condensation counteracts epigenetic activation of gene expression. Subsequent post‐mitotic re‐activation of transcription depends on epigenetic DNA and histone modifications, as well as other architecturally bound proteins that "bookmark" the genome. Osteogenic lineage commitment, differentiation and progenitor proliferation require the bone‐related runt‐related transcription factor Runx2. Here, we characterized a non‐genomic mRNA mediated mechanism by which osteoblast precursors retain their phenotype during self‐renewal. We show that osteoblasts produce maximal levels of Runx2 mRNA, but not protein, prior to mitotic cell division. Runx2 mRNA partitions symmetrically between daughter cells in a non‐chromosomal tubulin‐containing compartment. Subsequently, transcription‐independent de novo synthesis of Runx2 protein in early G1 phase results in increased functional interactions of Runx2 with a representative osteoblast‐specific target gene (osteocalcin/BGLAP2) in chromatin. Somatic transmission of Runx2 mRNAs in osteoblasts and osteosarcoma cells represents a versatile mechanism for translational rather than transcriptional induction of this principal gene regulator to maintain osteoblast phenotype identity after mitosis. J. Cell. Physiol. 231: 1001–1014, 2016. © 2015 Wiley Periodicals, Inc.